Understanding life paths (re)viewed by elderly people in their late phases of life: an achievement (Research, Society and Development, 2025)
This work aims to: Understand, according to their perceptions, aspects of the life projects of elderly people, which would be reaffirmed or, if possible, re-edited by them. This qualitative research brings is based on the narratives of six elderly people, aged between 63 and 90 years, three males and three females, facing the following question: "If you had the possibility to live again the time you lived until now, what would you do differently and what would you do the same way? Tell us about these paths.” Lewin's topological psychology provided support for the method of analysis of the aforementioned work by enabling the representations of these vital spaces described by the participants, as well as Erikson's theory. From the analysis, the following dimensions emerged: socioeconomic-educational condition; religiosity/spirituality; work/profession; family; relationship networks; life project; generativity; integrity and transgenicity. Such dimensions reflect peculiar dynamics of n the locomotion in their spaces, bringing taking them to a balance of what they had already been experienced as well as what they are experiencing in view of their visions of the future. Spirituality was outstanding in their speeches, revealing an unmistakable confidence, when referring to God in their paths. Integrity, an Eriksonian root dimension, also proved to be aligned in the perceptions of their paths, as they very often stated: “I would do everything the same way again”. We understand that there is a strong meaning for each journey narrated: an achievement.